The Chinese version of patient-doctor-relationship questionnaire (PDRQ-9): Factor structure, validation, and IRT psychometric analysis - Wang, Yufei; Wu, Aoxue; Jiang, Yinan; Duan, Yanping; Geng, Wenqi; Wan, Lin; Li, Jiarui; Du, Jianhua; Hu, Jiaojiao; Jiang, Jing; Shi, Lili; Wei, Jing (Frontiers in Psychiatry, 2023)
Objective The patient-doctor relationship has been considered as a crucial concept in primary healthcare, while the medical reform launched by the Chinese government in 2009 has brought significant changes to the healthcare system, which made it urgent to introduce reliable measurement instruments for assessing today’s doctor-patient relationship in China. This study examined the psychometric properties of the Chinese version of the Patient-Doctor-Relationship Questionnaire-9 item (PDRQ-9) scale among general hospital inpatients in China. Materials and methods A total of 203 participants responded to the survey, of which 39 completed retest after 7 days. Factor analyses were used to test the construct validity of the scale. Convergent validity was evaluated by the correlation between PDRQ-9 and depressive symptoms measured using PHQ-9 (Patient Health Questionnaire Depression Scale-9 item). Both multidimensional item response theory (MIRT) and unidimensional item response theory (IRT) framework were used to estimate the parameters of each item. Results The two-factor model of relationship quality and treatment quality was supported (χ2/df = 1.494, GFI = 0.925, RMSEA = 0.071, RMR = 0.008, CFI = 0.985, NFI = 0.958, NNFI = 0.980, TLI = 0.980, IFI = 0.986). The PDRQ-9 and both subscales showed significant correlation with PHQ-9 (r = −0.196∼−0.309) and good internal consistency (Cronbach’s alpha = 0.865∼0.933). ANCOVA analysis adjusted with age revealed significant difference in PDRQ-9 ratings between patients with or without significant depressive symptoms (P = 0.019). The 7-day test-retest reliability of the scale was 0.730. The MIRT model of full scale and IRT models of both subscales showed high discrimination of all items (a = 2.46∼38.46), and the test information within the range of low-quality relationship was relatively high. Conclusion The Chinese version of PDRQ-9 is a valid and reliable rating scale, which can measure the doctor-patient relationship among Chinese patients.